Practical resuscitation for healthcare professionals - Moule, Pam.; Albarran, John W.; Wiley eBooks (Chichester, U.K. ; Malden, MA : Wiley-Blackwell, 2009)
Practical Resuscitation for Healthcare Professionals is a beginner's guide to practical resuscitation which enables students and newly qualified staff to develop key resuscitation knowledge and skills. It reflects current guidelines and developments in resuscitation, including the 2005 European Resuscitation Council Guidelines for Resuscitation. Practical Resuscitation for Healthcare Professionals covers adult, paediatric and trauma resuscitation and addresses current legal and ethical issues including family witnessed resuscitation.: Revised in accordance with the '2005 European Resuscitation.
Resuscitation policy and educational developments -- Professional, ethical and legal issues -- Recognizing the critically ill patient and preventing cardiorespiratory arrest -- Resuscitation equipment -- Chain of survival -- Adult basic life support algorithm -- The advanced life support algorithm -- Paediatric life support -- Management of the airway and breathing -- Monitoring and assessing cardiac rhythms -- Defibrillation theory and practice -- Drugs and delivery -- Management of potentially reversible causes of cardiac arrest -- Post-resuscitation care -- Special circumstances -- Resuscitation of the seriously injured casualty -- Out-of-hospital resuscitation.
Revised edition of: Practical resuscitation : recognition and response / edited by Pam Moule and John W. Albarran. c2005.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Resuscitation; Emergency nursing; MEDICAL -- Nursing -- Emergency; MEDICAL -- Emergency Medicine; MEDICAL -- Allied Health Services -- Emergency Medical Services; Emergency nursing; Resuscitation; Resuscitation -- methods; Emergency Treatment -- methods; Electronic books